Effect of Measurement Factors on Photovoltaic Cell Parameters Extracting - El Hadi Chahid; Mohammed Idali Oumhand; M’barek Feddaoui; Mohammed Erritali; Abdessamad Malaoui (Institute of Advanced Engineering and Science, 2017)
In this paper, we study the influence of external factors on the measurement for the current–voltage (I-V) characteristic of the photovoltaic cell. These factors are the size of the number of measurements, the range of the cell generated voltage and the influence of measures step and mode combination of photovoltaic cells (parallel, serial, or hybrid). The main extracted parameters solar cell are the photocurrent Iph, the reverse diode saturation current I0, the ideality factor of diode n, the series resistance Rs and the shunt resistance Rsh. A method for finding these parameters, according to the single-diode model, was developed by Newton-Raphson’s method using Matlab. To assess the accuracy of this method, measured and calculated I–V characteristics were compared with provided data by the manufacturer at standard test condition (STC). The measurement results showed that these parameters are highly dependent on these four factors.